On-line monitoring of photosynthetic activity based on pH data to assess microalgae cultivation. (15th December 2020) - González-Camejo, J.; Robles, A.; Seco, A.; Ferrer, J.; Ruano, M.V.
Abstract: Microalgae performance of outdoor cultivation systems is influenced by environmental and operating dynamics. Monitoring and control systems are needed to maximise biomass productivity and nutrient recovery. The goal of this work was to corroborate that pH data could be used to monitor microalgae performance by means of data from an outdoor membrane photobioreactor (MPBR) plant. In this system, microalgae photosynthetic activity was favoured over other physical and biological processes, so that the pH data dynamics was theoretically related to the microalgae carbon uptake rate (CUR). Short- and long-term continuous operations were tested to corroborate the relationship between the first derivate of pH data dynamics (pH') and microalgae photosynthetic activity. Short-term operations showed a good correlation between gross pH' values and MPBR performance. An indicator of the maximum daily average microalgae activity was assessed by a combination of on-line pH' measurements obtained in the long-term and a microalgae growth kinetic model. Both indicators contributed to the development of advanced real-time monitoring and control systems to optimise microalgae cultivation technology. Graphical abstract: Image 1 Highlights: pH' data was used as an indicator of microalgae photosynthetic activity. Short-term operations showed a correlation between gross pH' and MPBR performance. Algae activity during MPBR operation was assessed combining pH' and kinetic model. PLS analysis corroborated the relation between pH' and MPBR performance.